Gender Inequality in Enrolment for Accountancy Programme in Nigeria Federal Polytechnics: Emerging Issues in Education - SOLANKE, Abiola Abosede (KABARAK UNIVERSITY, 2018)
Gender inequality exists all over the world, in access to and control of vital resources, in educational, economic and political opportunities. This paper investigates gender differences in enrollment pattern for Accountancy programme in Nigeria Federal polytechnics. The National Bureau of Statistics (NBS) obtained data from the 2011, and 2012 editions of Annual Abstract of Statistics Published. Data were analyzed using descriptive statistical methods. Percentages were used to describe annual changes in enrolment. Sex ratio was used to quantify the gender dimension of enrolment. Result show that in all academic sessions examined, males are consistently more in enrolment than females: more females are consistently enrolled at the ND level than the HND level. This paper suggested that current efforts to-rebrand the Nigeria education system must take cognizance of the level of disparities between males and females for all programmes at the tertiary education level; and devise means of bridging the gender gap
FULL TEXT
Keywords: Gender; Enrolment; Accountancy; Education; Inequality